What Determine Ragpickers’ Movement and Location Selection? – A Qualitative Study in Depok City - Putri Intan Adella; Triarko Nurlambang; Hafid Setiadi (Proceedings of AICS - Social Sciences, 2017)
Ragpickers (or pemulung) move from one location to another to collect garbage. This study was conducted with an objective to analysis the movement and location selection decision of ragpickers in Depok City, Indonesia. This qualitative based research was carried on 10 working sites of ragpickers located in 3 sub-districts (kecamatan) in Depok City. Data was collected through observation and in-depth interviews with 13 selected ragpickers. Secondary data was obtained from 2014 land use map of Depok, demography report and waste management regulation in Depok Government. The data was analyzed by using qualitative data method. This study found that ragpickers determine main location and alternative locations. Their working location selection is decided based on some factors i.e. location characteristics and individual preferences. The location characteristics are the operational time of the waste picker, the community's habit of choosing the waste, and the rules within the location. Meanwhile, the individual preferences are distance, time and competition among ragpickers. The choice of location is linked to gender identity and the length of ragpickers experience. This study also found that the more experienced ragpickers moved to landfills within certain times, whereas less experienced ragpickers choice different working location to avoid competition.